If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + 12 = -6s + 6 Reorder the terms: 12 + 3s = -6s + 6 Reorder the terms: 12 + 3s = 6 + -6s Solving 12 + 3s = 6 + -6s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '6s' to each side of the equation. 12 + 3s + 6s = 6 + -6s + 6s Combine like terms: 3s + 6s = 9s 12 + 9s = 6 + -6s + 6s Combine like terms: -6s + 6s = 0 12 + 9s = 6 + 0 12 + 9s = 6 Add '-12' to each side of the equation. 12 + -12 + 9s = 6 + -12 Combine like terms: 12 + -12 = 0 0 + 9s = 6 + -12 9s = 6 + -12 Combine like terms: 6 + -12 = -6 9s = -6 Divide each side by '9'. s = -0.6666666667 Simplifying s = -0.6666666667
| -1.1+u=8 | | 20x-1=4(5x+6) | | 54=(4x-6) | | 4y-8+y=46+3y-4y | | -12+5x=3(x-2) | | b+3b+b+b= | | 5x+6+2x=7x-6 | | 2-a=-8 | | 5x-22+2x=20 | | -29=8+4(c+3) | | 11m-6m=22 | | kn+mp=qforp | | 3(2x-5)=9x+15 | | 40x-15=15x+39 | | 63+(2x+9)=180 | | 2(5x+1)+4=36 | | W+5w+w+w= | | 1.9+3.4=w | | 4x+11x-1=3(5x+9) | | 4x-(3x-1)=-x+12 | | ax-bx=y | | 18-30x-48=-24 | | 40x+4=3x-1 | | -3n^2+11n+28=-4n^2 | | 2x+5y=3y | | x+1*4-11=2x | | 2(x)-y=-65 | | -256a^2+36= | | 36=2(6+x) | | 4(8-3r)=-33 | | 8+2a+a=3a+2 | | 32.63=7g+3.65 |